Photocatalytic performance of hybrid aerogels for wastewater treatment - Tiwari H.; Singh R.S. (My University, 2025)
The emerging global water crisis demands innovative strategies to address the escalating challenges of wastewater treatment. In the pursuit of sustainable solutions for wastewater treatment, the amalgamation of advanced photocatalytic materials with hybrid aerogels has emerged as a promising frontier. Aerogels, renowned for their exceptional properties, have shown promising potential for efficient pollutant degradation when integrated with photocatalytic materials. They exhibit high surface area, low density, and variable porosity, which allow for synergistic effects with photocatalysis to create hybrid materials with enhanced photocatalytic performance. The present study comprehensively explores the integration of photocatalytic materials along with hybrid aerogels as an innovative technique for wastewater treatment. Moreover, the fabrication methods of aerogels and foundational properties are reviewed. As challenges and opportunities converge, collaborative interdisciplinary efforts are poised to drive the practical implementation of hybrid aerogels in real-world applications. The potential of hybrid aerogels in diverse wastewater treatment scenarios is critically reviewed along with their synergistic effects and underlying mechanisms. This chapter presents recent advancements, challenges, and opportunities in hybrid aerogels, emphasizing the need for sustainable and effective solutions to address water pollution. © 2024 Walter de Gruyter GmbH, Berlin/Boston. All rights reserved.